Epidemiology and Clinical Characteristics of Presumed Ocular Histoplasmosis in Olmsted County, Minnesota. (4th July 2022) - Xu, Timothy T.; Reynolds, Margaret M.; Hodge, David O.; Smith, Wendy M.
ABSTRACT: Purpose: To describe the incidence, prevalence, and clinical characteristics of presumed ocular histoplasmosis syndrome (POHS) in a Histoplasma endemic region. Methods: The International Classification of Diseases, 9 th and 10 th Revision codes were used to search the Rochester Epidemiology Project, a record-linkage system for medical care provided in Olmsted County, MN. Medical records were reviewed to confirm POHS diagnoses in county residents from January 1, 2006, to December 31, 2015. Age- and sex-adjusted incidence rates were calculated and adjusted to the 2010 U.S. White population. Results: There were 18 incident cases (30 eyes) and 87 prevalent cases (131 eyes). The incidence rate was 1.35 per 100, 000 per year. The mid-study prevalence rate was 0.064%. Choroidal neovascularization (CNV) occurred in 17.4% of the affected eyes. At the last follow-up, 16.8% of the affected eyes had POHS-related decreased visual acuity (<20/40). Conclusion: This study assesses the epidemiology and clinical features of POHS in a Midwestern U.S. county. ABBREVIATIONS/ACRONYMS: POHS = Presumed ocular histoplasmosis syndrome; ICD = International Classification of Diseases; CI = Confidence interval; VA = Visual acuity; Anti-VEGF = Anti-vascular endothelial growth factor; REP = Rochester Epidemiology Project, CNV = Choroidal neovascularization.